The molecular mechanism of hydrogen bond formation between t-a base pairs within a promoter and a sigma factor - Kurchii, B.A. (Фактори експериментальної еволюції організмів, 2009)
In this report it is described the molecular mechanisms of a promoter (a gene lock) and a sigma factor (a gene key) interaction during transcription reaction. The hydrogen bond is formed between the hydrogen at N6 of the adenine and the oxygen at C2 of the thymine. This process leads to the separation of doubled strands of DNA in the gene lock into two single strands of DNA and transcription initiation.